Biochar recycled concrete and preparation method thereof

By using biochar and CO2 pressure treatment prepared by low oxygen pyrolysis in recycled concrete, the problems of low carbon fixation efficiency and unstable composition of recycled concrete are solved, and its compressive strength and carbon fixation amount are significantly improved, and resource recovery is achieved and cost savings.

CN119241155APending Publication Date: 2025-01-03CHENGDU UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411372556.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Recycled concrete faces the problems of low carbon sequestration efficiency and unstable composition, which affects its mechanical and durability.

Method used

Biochar is prepared by low oxygen pyrolysis, and biochar is prepared at an appropriate pyrolysis temperature. Combined with the use of CO2 pressure during carbonization and curing, carbon is enhanced by using carbonization and curing. Adsorption and carbon sequestration capability.

Benefits of technology

The compressive strength and carbon sequestration of recycled concrete are improved, its stability and durability are enhanced, and resource recycling and cost savings are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses charcoal recycled concrete and a preparation method thereof, and belongs to the technical field of building materials. The biochar recycled concrete provided by the invention is prepared from the following components in parts by mass: 400 to 420 parts of cement, 40 to 50 parts of biochar, 600 to 620 parts of natural sand, 1000 to 1200 parts of recycled coarse aggregate and 200 to 210 parts of water, the recycled concrete has high compressive strength and high carbon sequestration amount, and the carbon sequestration capacity of the recycled concrete is greatly improved. The preparation method is simple and convenient, materials are easy to obtain, production is easy, and the method has excellent industrial prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to biochar regenerated concrete and a preparation method thereof. Background Art

[0002] With the rapid development of urbanization and industrialization in human society, carbon dioxide emissions are also increasing sharply. Carbon capture and storage technology is an effective way to reduce carbon dioxide emissions. Carbon storage technology refers to the state in which the carbon dioxide captured in the two processes of carbon capture and carbon transportation is kept isolated from the atmosphere for a long period of time.

[0003] After carbonization curing, recycled concrete can effectively improve its mechanical and durability properties, but at present, recycled concrete still faces problems such as low carbon fixation efficiency and unstable composition. Therefore, it is very important to improve the carbonation conversion efficiency of recycled concrete. Low-oxygen pyrolysis of discarded agricultural biomass raw materials into biochar can not only improve the environment, but also bring effective carbon sequestration benefits through long-term decarbonization. The pore volume and specific surface area of ​​biochar at different pyrolysis temperatures are affected, which in turn affects the water absorption and water retention capacity, as well as the CO2 adsorption capacity, which in turn affects the carbon fixation amount and compressive strength of recycled concrete. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention provides a biochar regenerated concrete and a preparation method thereof, which solves the problems of low carbon fixation efficiency and unstable composition faced by the prior art regenerated concrete.

[0005] In order to achieve the above-mentioned object, the technical solution adopted by the present invention is: to provide a biochar regenerated concrete, comprising the following components in parts by weight: 400-420 parts of cement, 40-50 parts of biochar, 600-620 parts of natural sand, 1000-1200 parts of recycled coarse aggregate and 200-210 parts of water.

[0006] The beneficial effects of the present invention are as follows: the present invention combines recycled concrete with biochar to make it have high compressive strength and high carbon fixation; biochar itself has a high specific surface area and a high affinity for non-polar compounds, and the biochar recycled concrete prepared at a suitable pyrolysis temperature will enable it to have better carbon adsorption and carbon sequestration capabilities. When CO2 enters the interior of the recycled concrete, many alkaline hydration products (such as Ca(OH)2) contact with a large amount of CO2 to produce CaCO3, which increases the carbon fixation amount. In addition, there are many pores and microcracks on the surface of the recycled aggregate, and many hydration products (such as CSH) will also contact with CO2 to produce more CaCO3 precipitation, which can enhance the surface strength of the recycled aggregate, reduce water absorption, and help improve the stability and durability of the recycled concrete.

[0007] Based on the above technical solution, the present invention can also be improved as follows.

[0008] Further, the cement includes the following components in mass percentage: 63.31% CaO, 20.57% SiO, 5.32% Al2O3, 3.77% Fe2O3, 1.41% MgO, 0.81% K2O, 2.12% SO3 and 0.18% Na2O.

[0009] Furthermore, the biochar is obtained by low-oxygen pyrolysis of rice straw and then passing through a 200-mesh sieve; the low-oxygen pyrolysis process is: temperature 400~700℃, oxygen concentration 3%.

[0010] Furthermore, the specific surface area of ​​biochar is 189~266m 2 / g, micropore volume is 0.035~0.066cm 3 / g.

[0011] The beneficial effect of adopting a further technical solution is that by preparing biochar through low-oxygen pyrolysis of rice straw, resource recycling is achieved, environmental pollution caused by agricultural waste is reduced, and biochar with a rich pore structure is obtained.

[0012] Furthermore, the recycled coarse aggregate is waste concrete particles with a particle size of 4.75 to 19 mm.

[0013] The beneficial effects of adopting further technical solutions are: achieving the recycling of waste resources, saving costs and improving industrial prospects.

[0014] The present invention also discloses a method for preparing biochar regenerated concrete, comprising the following steps: S1: Mix biochar, cement and natural sand evenly, then add half of water and stir at a speed of 10-15 r / min for 5 minutes to obtain a premix; S2: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 10-15 r / min for 5 min to obtain a mixed slurry; S3: pouring the mixed slurry into a mold and curing it for 24 hours before demoulding, and then placing it in a constant temperature curing box for pre-curing to obtain a crude product; S4: Place the crude product under vacuum conditions for 1 minute, then introduce CO2 gas and maintain the CO2 pressure at 0.05-0.5 MPa. Curing for 2 hours will yield biochar-regenerated concrete.

[0015] Furthermore, the pre-curing is performed at 21-25°C and 55-65% humidity for 72 hours.

[0016] The beneficial effect of the present invention is that in the early material mixing stage of the preparation method provided by the present invention, the biochar absorbs additional free water through its water absorption property and stores the water through the pores. During the later hydration process, the water inside the biochar is gradually released, and the water can be used to promote internal hydration. The biochar prepared at a suitable pyrolysis temperature helps to independently perform internal maintenance in the absence of external water, which makes the biochar an internal curing agent for cement hydration. The efficient hydration process makes the recycled concrete have better mechanical properties. DETAILED DESCRIPTION

[0017] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0018] Example 1 A biochar recycled concrete comprises the following components in parts by weight: 406 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 45 parts of biochar, 611.5 parts of natural sand, 1135.6 parts of recycled coarse aggregate (waste concrete particles with a particle size of 9.5 mm), and 203 parts of water.

[0019] In this embodiment, the biochar regenerated concrete is prepared by the following steps: S1: Biochar (specific surface area 224m 2 / g, micropore volume 0.05cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 12r / min for 5min to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 12 r / min for 5 min to obtain a mixed slurry; S4: pour the mixed slurry into a mold and cure it for 24 hours before demoulding. After demoulding, put it into a constant temperature curing box and cure it at 23°C and 60% humidity for 72 hours to obtain a crude product; S5: Place the crude product in a curing barrel, turn on the vacuum pump to evacuate the barrel, maintain the vacuum for 1 minute, then introduce CO2 gas and maintain the CO2 pressure at 0.05 MPa. Curing for 2 hours, obtain biochar regenerated concrete.

[0020] Example 2 A biochar recycled concrete comprises the following components in parts by weight: 400 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 40 parts of biochar, 600 parts of natural sand, 1100 parts of recycled coarse aggregate (waste concrete particles with a particle size of 4.75 mm), and 200 parts of water.

[0021] In this embodiment, the biochar regenerated concrete is prepared by the following steps: S1: Biochar (specific surface area 224m 2 / g, micropore volume 0.05cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 10r / min for 5 minutes to obtain a premix; S3: adding recycled coarse aggregate and remaining water to the premix, stirring at a speed of 10 r / min for 5 min to obtain a mixed slurry; S4: Pour the mixed slurry into a mold and cure it for 24 hours before demoulding. After demoulding, put it into a constant temperature curing box and cure it at 21°C and 65% humidity for 72 hours to obtain a crude product; S5: Place the crude product in a curing barrel, start the vacuum pump to evacuate the barrel, maintain it for 1 minute, then introduce CO2 gas and maintain the CO2 pressure at 0.2 MPa. Curing for 2 hours, obtain biochar regenerated concrete.

[0022] Example 3 A biochar recycled concrete comprises the following components in parts by weight: 420 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 50 parts of biochar, 620 parts of natural sand, 1200 parts of recycled coarse aggregate (waste concrete particles with a particle size of 19 mm), and 210 parts of water.

[0023] In this embodiment, the biochar regenerated concrete is prepared by the following steps: S1: Biochar (specific surface area 224m 2 / g, micropore volume 0.05cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 15r / min for 5 minutes to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 15 r / min for 5 min to obtain a mixed slurry; S4: pour the mixed slurry into a mold and cure it for 24 hours before demoulding. After demoulding, put it into a constant temperature curing box and cure it at 25°C and 55% humidity for 72 hours to obtain a crude product; S5: Place the crude product in a curing barrel, start the vacuum pump to evacuate the barrel, maintain it for 1 minute, then introduce CO2 gas and maintain the CO2 pressure at 0.35 MPa. Curing for 2 hours, obtain biochar regenerated concrete.

[0024] Example 4 A biochar recycled concrete comprises the following components in parts by weight: 406 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 45 parts of biochar, 611.5 parts of natural sand, 1135.6 parts of recycled coarse aggregate (waste concrete particles with a particle size of 16 mm), and 203 parts of water.

[0025] In this embodiment, the biochar regenerated concrete is prepared by the following steps: S1: Biochar (specific surface area 224m 2 / g, micropore volume 0.05cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 12r / min for 5min to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 12 r / min for 5 min to obtain a mixed slurry; S4: pour the mixed slurry into a mold and cure it for 24 hours before demoulding. After demoulding, put it into a constant temperature curing box and cure it at 23°C and 60% humidity for 72 hours to obtain a crude product; S5: Place the crude product in a curing barrel, start the vacuum pump to evacuate the barrel, maintain it for 1 minute, then introduce CO2 gas and maintain the CO2 pressure at 0.5 MPa. Curing for 2 hours, obtain biochar regenerated concrete.

[0026] Example 5 A biochar recycled concrete comprises the following components in parts by weight: 406 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 45 parts of biochar, 611.5 parts of natural sand, 1135.6 parts of recycled coarse aggregate (waste concrete particles with a particle size of 9.5 mm), and 203 parts of water.

[0027] In this embodiment, the biochar regenerated concrete is prepared by the following steps: S1: Biochar (specific surface area 266m 2 / g, micropore volume 0.066cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 12r / min for 5min to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 12 r / min for 5 min to obtain a mixed slurry; S4: pour the mixed slurry into a mold and cure it for 24 hours before demoulding. After demoulding, put it into a constant temperature curing box and cure it at 23°C and 60% humidity for 72 hours to obtain a crude product; S5: Place the crude product in a curing barrel, turn on the vacuum pump to evacuate the barrel, maintain the vacuum for 1 minute, then introduce CO2 gas and maintain the CO2 pressure at 0.05 MPa. Curing for 2 hours, obtain biochar regenerated concrete.

[0028] Example 6 A biochar regenerated concrete, which differs from Example 5 in that the CO2 curing pressure is 0.2 MPa.

[0029] Example 7 A biochar regenerated concrete, which differs from Example 5 in that the CO2 curing pressure is 0.35 MPa.

[0030] Example 8 A biochar regenerated concrete, which differs from Example 5 in that the CO2 curing pressure is 0.5 MPa.

[0031] Example 9 A biochar recycled concrete comprises the following components in parts by weight: 406 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 45 parts of biochar, 611.5 parts of natural sand, 1135.6 parts of recycled coarse aggregate (waste concrete particles with a particle size of 9.5 mm), and 203 parts of water.

[0032] In this embodiment, the biochar regenerated concrete is prepared by the following steps: S1: Biochar (specific surface area 242m2) was obtained by pyrolysis of rice straw at 600℃ under the condition of 3% oxygen concentration and then screened through a 200-mesh screen. 2 / g, micropore volume 0.057cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 12r / min for 5min to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 12 r / min for 5 min to obtain a mixed slurry; S4: pour the mixed slurry into a mold and cure it for 24 hours before demoulding. After demoulding, put it into a constant temperature curing box and cure it at 23°C and 60% humidity for 72 hours to obtain a crude product; S5: Place the crude product in a curing barrel, turn on the vacuum pump to evacuate the barrel, maintain the vacuum for 1 minute, then introduce CO2 gas and maintain the CO2 pressure at 0.05 MPa. Curing for 2 hours, obtain biochar regenerated concrete.

[0033] Example 10 A biochar regenerated concrete, which differs from Example 9 in that the CO2 curing pressure is 0.2 MPa.

[0034] Embodiment 11 A biochar regenerated concrete, which differs from Example 9 in that the CO2 curing pressure is 0.35 MPa.

[0035] Example 12 A biochar regenerated concrete, which differs from Example 9 in that the CO2 curing pressure is 0.5 MPa.

[0036] Embodiment 13 A biochar recycled concrete comprises the following components in parts by weight: 406 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 45 parts of biochar, 611.5 parts of natural sand, 1135.6 parts of recycled coarse aggregate (waste concrete particles with a particle size of 9.5 mm), and 203 parts of water.

[0037] In this embodiment, the biochar regenerated concrete is prepared by the following steps: S1: Biochar (specific surface area 189m 2 / g, micropore volume 0.035cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 12r / min for 5min to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 12 r / min for 5 min to obtain a mixed slurry; S4: pour the mixed slurry into a mold and cure it for 24 hours before demoulding. After demoulding, put it into a constant temperature curing box and cure it at 23°C and 60% humidity for 72 hours to obtain a crude product; S5: Place the crude product in a curing barrel, turn on the vacuum pump to evacuate the barrel, maintain the vacuum for 1 minute, then introduce CO2 gas and maintain the CO2 pressure at 0.05 MPa. Curing for 2 hours, obtain biochar regenerated concrete.

[0038] Embodiment 14 A biochar regenerated concrete, which differs from Example 13 in that the CO2 curing pressure is 0.2 MPa.

[0039] Embodiment 15 A biochar regenerated concrete, which differs from Example 13 in that the CO2 curing pressure is 0.35 MPa.

[0040] Example 16 A biochar regenerated concrete, which differs from Example 13 in that the CO2 curing pressure is 0.5 MPa.

[0041] Comparative Example 1 A biochar recycled concrete comprises the following components in parts by weight: 406 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 45 parts of biochar, 611.5 parts of natural sand, 1135.6 parts of recycled coarse aggregate (waste concrete particles with a particle size of 9.5 mm), and 203 parts of water.

[0042] The biochar regenerated concrete in this comparative example is prepared by the following steps: S1: Biochar (specific surface area 224m 2 / g, micropore volume 0.05cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 12r / min for 5min to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 12 r / min for 5 min to obtain a mixed slurry; S4: Pour the mixed slurry into a mold and cure it for 24 hours before demolding. After demolding, put it into a constant temperature curing box and cure it at 23°C and 60% humidity for 72 hours to obtain biochar recycled concrete.

[0043] Comparative Example 2 A biochar recycled concrete comprises the following components in parts by weight: 406 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 45 parts of biochar, 611.5 parts of natural sand, 1135.6 parts of recycled coarse aggregate (waste concrete particles with a particle size of 9.5 mm), and 203 parts of water.

[0044] The biochar regenerated concrete in this comparative example is prepared by the following steps: S1: Biochar (specific surface area 266m 2 / g, micropore volume 0.066cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 12r / min for 5min to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 12 r / min for 5 min to obtain a mixed slurry; S4: Pour the mixed slurry into a mold and cure it for 24 hours before demolding. After demolding, put it into a constant temperature curing box and cure it at 23°C and 60% humidity for 72 hours to obtain biochar recycled concrete.

[0045] Comparative Example 3 A biochar recycled concrete comprises the following components in parts by weight: 406 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 45 parts of biochar, 611.5 parts of natural sand, 1135.6 parts of recycled coarse aggregate (waste concrete particles with a particle size of 9.5 mm), and 203 parts of water.

[0046] The biochar regenerated concrete in this comparative example is prepared by the following steps: S1: Biochar (specific surface area 242m2) was obtained by pyrolysis of rice straw at 600℃ under the condition of 3% oxygen concentration and then screened through a 200-mesh screen. 2 / g, micropore volume 0.057cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 12r / min for 5min to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 12 r / min for 5 min to obtain a mixed slurry; S4: Pour the mixed slurry into a mold and cure it for 24 hours before demolding. After demolding, put it into a constant temperature curing box and cure it at 23°C and 60% humidity for 72 hours to obtain biochar recycled concrete.

[0047] Comparative Example 4 A biochar recycled concrete comprises the following components in parts by weight: 406 parts of cement (the components are 63.31wt% CaO, 20.57wt% SiO, 5.32wt% Al2O3, 3.77wt% Fe2O3, 1.41wt% MgO, 0.81wt% K2O, 2.12wt% SO3, and 0.18wt% Na2O), 45 parts of biochar, 611.5 parts of natural sand, 1135.6 parts of recycled coarse aggregate (waste concrete particles with a particle size of 9.5 mm), and 203 parts of water.

[0048] The biochar regenerated concrete in this comparative example is prepared by the following steps: S1: Biochar (specific surface area 189m 2 / g, micropore volume 0.035cm 3 / g); S2: Mix the biochar, cement and natural sand evenly, then add half of water and stir at a speed of 12r / min for 5min to obtain a premix; S3: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 12 r / min for 5 min to obtain a mixed slurry; S4: Pour the mixed slurry into a mold and cure it for 24 hours before demolding. After demolding, put it into a constant temperature curing box and cure it at 23°C and 60% humidity for 72 hours to obtain biochar recycled concrete.

[0049] Experimental Example 1 Carbon fixation test: The amount of CO2 absorbed by recycled concrete during carbonation curing is expressed as the amount of carbon fixation per kg of concrete. During the carbonation reaction, CO2 reacts with the hydration products inside the concrete to generate carbonation products and water. The carbonation products are generated inside the test block, which increases the mass of the test block. The mass change of the remaining water can be expressed by the mass change of the vacuum pressure barrel before and after carbonation. Therefore, before carbonation curing, weigh the mass of the test block before the reaction and the mass of the vacuum pressure barrel to obtain the masses M1 and M2. W1 After carbonization curing, weigh the mass of the test block and the mass of the vacuum pressure barrel to obtain M2 and M W2 , subtract the total mass before carbonization from the total mass after carbonization to get the total mass of CO2 absorbed by the test block during the carbonization reaction. Since there are slight differences in the masses of different test blocks, it is necessary to divide the total mass obtained by the mass of the test block before carbonization M1 to get the unit carbon fixation amount M per kg of test block. c , the test results are shown in Table 1.

[0050]

[0051] Table 1 Carbon fixation test results

[0052] As can be seen from Table 1, comparing Examples 1-4, Examples 5-8, Examples 9-12, and Examples 13-16, the carbonation pressure during carbonation curing has a certain influence on the carbon fixation amount of biochar regenerated concrete. Since increasing the CO2 pressure will promote the faster diffusion of CO2 into the concrete, many alkaline hydration products contact a large amount of CO2 to produce CaCO3, resulting in a rapid increase in the carbon fixation amount of each group of test blocks. The increase in carbonation pressure causes the carbon fixation amount to increase first and then tend to be flat, so Example 4 has a higher carbon fixation amount.

[0053] As can be seen from Table 1, by comparing Example 3, Example 7, Example 11 and Example 15, the biochar pyrolysis temperature has a certain influence on the biochar regenerated concrete. The biochar pyrolysis temperature makes the biochar promote the hydration reaction to different degrees, resulting in different rates of carbonization reaction. In addition, different pyrolysis temperatures have different specific surface areas and pore volumes, resulting in different CO2 adsorption capacities. Therefore, Example 7 has a higher carbon fixation amount.

[0054] Experimental Example 2 Compressive strength test: According to the compressive strength test in GB / T 50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the 28d compressive strength (MPa) of concrete was tested. The test results are shown in Table 2.

[0055] Table 2 Compressive strength test results

[0056] As shown in Table 2, by comparing Examples 1-4 with Comparative Example 1, Examples 1-4 were carbonized and cured, while Comparative Example 1 was not carbonized. Examples 1-4 obtained higher strengths. This is because during the carbonization curing process, the Ca2+ dissolved by cement hydration 2+ CO3 in H2CO3 produced by dissolving CO2 in water 2- The CaCO3 precipitate generated by the opposite reaction continuously fills the pore structure of the recycled concrete, and the carbonization reaction process also causes CSH to decalcify and generate high-polymerization silica gel, thereby improving the density of the recycled concrete and further increasing the compressive strength.

[0057] As can be seen from Table 2, comparing Examples 1-4, 5-8, 9-12, and 13-16, the carbonization curing pressure has a certain effect on biochar regenerated concrete, but the greater the better. The appropriate carbonization curing pressure is conducive to improving the compressive strength. Because in the early stage of the carbonization reaction, due to the high CO2 pressure, the hydration products react rapidly with CO2, and the rapid formation of CaCO3 causes the porosity of the surface layer of the test block to decrease rapidly, and the compressive strength is greatly affected by the porosity, so it is significantly improved. However, as the carbonization reaction continues, the pores and cracks are gradually blocked, and the surfaces of all CaCO3 are gradually passivated, which slows down the further diffusion of CO2, and the carbonization reaction rate gradually decreases, and the compressive strength improvement becomes gentle or even decreases.

[0058] As can be seen from Table 2, by comparing Example 3, Example 7, Example 11 and Example 15, Example 7 has the largest compressive strength, indicating that the appropriate pyrolysis temperature can effectively improve the mechanical properties of biochar regenerated concrete. Because biochar has different specific surface areas and pore volumes at different pyrolysis temperatures, the biochar of Example 7 has higher specific surface area and pore volume, so that the hydrophilic functional groups on its surface absorb more water during the stirring process, and can continuously release more water through the capillaries of the cement gel in the subsequent hydration process, promote the secondary hydration reaction, generate more hydration products, and thus improve the compressive strength.

[0059] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A biochar regenerated concrete, characterized in that: The invention comprises the following components in parts by weight: 400-420 parts of cement, 40-50 parts of biochar, 600-620 parts of natural sand, 1000-1200 parts of recycled coarse aggregate and 200-210 parts of water.

2. The biochar-regenerated concrete according to claim 1, characterized in that: The cement includes the following components in percentage by mass: 63.31% CaO, 20.57% SiO, 5.32% Al2O3, 3.77% Fe2O3, 1.41% MgO, 0.81% K2O, 2.12% SO3 and 0.18% Na2O.

3. The biochar regenerated concrete according to claim 1, characterized in that: The biochar is obtained by low-oxygen pyrolysis of rice straw and then passing through a 200-mesh screen; the low-oxygen pyrolysis process is as follows: temperature 400-700°C, oxygen concentration 3%.

4. The biochar regenerated concrete according to claim 3, characterized in that: The specific surface area of ​​the biochar is 189~266m 2 / g, micropore volume is 0.035~0.066cm 3 / g.

5. The biochar regenerated concrete according to claim 1, characterized in that: The recycled coarse aggregate is waste concrete particles with a particle size of 4.75-19 mm.

6. The method for preparing biochar-regenerated concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Mix biochar, cement and natural sand evenly, then add half of water and stir at a speed of 10-15 r / min for 5 minutes to obtain a premix; S2: Add recycled coarse aggregate and remaining water to the premix, stir at a speed of 10-15 r / min for 5 min to obtain a mixed slurry; S3: pouring the mixed slurry into a mold and curing it for 24 hours before demoulding, and performing pre-curing after demoulding to obtain a crude product; S4: Place the crude product under vacuum conditions for 1 minute, then introduce CO2 gas and maintain the CO2 pressure at 0.05-0.5 MPa. Curing for 2 hours will yield biochar-regenerated concrete.

7. The method for preparing biochar-regenerated concrete according to claim 6, characterized in that: The pre-curing is performed for 72 hours at 21-25°C and 55-65% humidity.

Citation Information

Patent Citations

  • Charcoal concrete

    CN107188478A

  • Carbon dioxide cured reinforced concrete and preparation method thereof

    CN115521107A

  • Biochar concrete and preparation method thereof

    CN115594448A

  • Novel environment-friendly recycled aggregate pervious concrete and preparation method thereof

    CN117263591A

  • Marine source biochar regenerated ecological concrete for environmental restoration

    CN117865596A

Cited By

  • Anti-scouring ecological concrete formula for slope protection

    CN120192129A